Age‐Related Effects on Social Cognition in Adults with Autism Spectrum Disorder: A Possible Protective Effect on Theory of Mind. Issue 5 (16th October 2020) - Zıvralı Yarar, Esra; Howlin, Patricia; Charlton, Rebecca; Happé, Francesca
Abstract : Impaired social cognition has been suggested to underlie the social communication difficulties that define autism spectrum disorder (ASD). In typical development, social cognition may deteriorate in older age, but age effects in ASD adults have been little explored. In the present study, we compared groups of younger and older adults with and without ASD ( n = 97), who completed a set of social cognition tasks assessing theory of mind (ToM), and self‐report measures of empathy and alexithymia. While typically developing (TD) younger adults outperformed elderly TD and younger ASD participants, younger and older ASD adults did not differ in their ToM performance, and the elderly ASD and TD groups performed equivalently. By contrast, ASD adults reported lower empathy scores and higher levels of alexithymia symptoms compared to TD adults regardless of age. The difference between ASD and TD groups in self‐reported empathy scores was no longer significant when alexithymia was covaried (with the exception of the Perspective Taking subscore). Results suggest a possible age‐protective effect on ToM in the ASD group. In addition, empathy difficulties appear to be associated with alexithymia rather than ASD per se. Possible interpretations are discussed, and future directions for autism aging research are proposed. Lay Summary: People with autism spectrum disorder (ASD) have difficulties with social understanding. Some age‐related studies in typical development have shown a decline in social understanding in older age. We investigated whether a similar pattern is present in adults with ASD. We found that understanding what someone is thinking was not worse in older versus younger autistic adults. Also, we reported further evidence suggesting that emotional empathy difficulties were related to difficulties with understanding one's own emotions rather than with autism itself. Autism Res 2021, 14: 911–920 . © 2020 International Society for Autism Research and Wiley Periodicals LLC.